Potential Pharmaceutical Biotechnology Products in the Form of Formulations and Preparations of Telang Flower Kombucha Dish Soap (Clitoria ternatea L) as an Antibacterial from Beef (Bos taurus) Isolate - Firman Rezaldi; Eva Nurvadilah; Candra Junaedi; Ucu Wandi Somantri; M. Fariz Fadillah; Vevi Maritha; Ratna Fitry Yenny; Diyan Yunanto Setyaji (Journal of Health and Nutrition Research, 2024)
This research aims to see the potential of each formulation and preparation of dishwashing soap with the active ingredient telang flower kombucha in inhibiting the growth of pathogenic bacteria isolated from beef. This research is a laboratory experiment, namely by making a dishwashing soap base without the active substance of telang flower kombucha. Make a dishwashing soap base that adds the active substance of butterfly pea flower kombucha at concentrations of 20%, 30% and 40%. Biochemical identification results have shown that beef samples contain gram-positive bacteria in the form of Staphylococcus aureus and Listeria monocytogenes, as well as gram-negative bacteria in the form of Salmonella thyposa and Escherichia coli. The results of this research have also proven that pharmaceutical biotechnology products in the form of formulations and dishwashing soap preparations with the active ingredient telang flower kombucha have a positive correlation in inhibiting the growth of the four test bacteria. Based on the one-way ANOVA statistical test at each P value <0.05, it proves that telang flower kombucha dish soap at a concentration of 40% according to post hoc analysis is not significantly different from concentrations of 20% and 30% as a pharmaceutical and antibacterial biotechnology product. isolated from beef. The conclusion of this research is that the formulation and preparation of dishwashing soap at a concentration of 40% proved to be the most effective as a pharmaceutical biotechnology product in inhibiting the growth of the four test bacteria.